2018
DOI: 10.3892/etm.2018.7134
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic utility of central damage determination in glaucoma by magnetic resonance imaging: An observational study

Abstract: The aim of the present study was to investigate the utility of diffusion tensor imaging (DTI) parameters of the central visual pathway and the size of the lateral geniculate nucleus (LGN) in the diagnosis of primary open-angle glaucoma (POAG). To test this, 24 POAG patients and 24 age-and gender-matched controls underwent 3.0 Tesla magnetic resonance imaging examinations, including DTI and LGN structural imaging. Receiver operating characteristic (ROC) curves were generated and Spearman's correlation coefficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 25 publications
0
20
0
Order By: Relevance
“…In the study by Furlanetto [ 34 ] of 3T MRI of LGN, however, the only parameter that showed a significant difference between glaucoma and control groups was the LGN height. Furthermore, at 3T Li [ 12 ] examined 24 POAG patients and 24 controls and concluded that for distinguishing glaucomatous eyes from healthy eyes, measurements of the LGN volume exhibited a high sensitivity and specificity. They also observed that the use of LGN volume differentiates glaucomatous patients from healthy controls only at the advanced stage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the study by Furlanetto [ 34 ] of 3T MRI of LGN, however, the only parameter that showed a significant difference between glaucoma and control groups was the LGN height. Furthermore, at 3T Li [ 12 ] examined 24 POAG patients and 24 controls and concluded that for distinguishing glaucomatous eyes from healthy eyes, measurements of the LGN volume exhibited a high sensitivity and specificity. They also observed that the use of LGN volume differentiates glaucomatous patients from healthy controls only at the advanced stage.…”
Section: Discussionmentioning
confidence: 99%
“…Li [ 12 ] showed that fractional anisotropy–an index derived from diffusion tensor imaging–can be a measure of glaucoma damage in the optic tract. Lee et al [ 13 ] performed volumetric measures of the LGN in 7T MR with proton density weighting.…”
Section: Introductionmentioning
confidence: 99%
“…Diffusion tensor imaging is the development and deepening of diffusion-weighted imaging, the only non-invasive examination method that can effectively observe and track the bundles of white matter fibers in the brain ( Li et al, 2019 ). The function change can be revealed by the parameters of DTI, such as radial diffusivity (λ⊥), axial diffusivity (λ ‖), and fractional anisotropy (FA).…”
Section: The Phenomenon Of Demyelinationmentioning
confidence: 99%
“…They are sensitive to high-frequency space and transmit red and green color information (Schiller and Malpeli, 1978 ; Hendry and Calkins, 1998 ; Masri et al, 2020 ). Several studies have shown that both the M and P layers of the LGN are damaged in monkey glaucoma models (Dandona et al, 1991 ; Chaturvedi et al, 1993 ; Vickers et al, 1997 ; Weber et al, 2000 ; Yucel et al, 2000 , 2001 ; Sasaoka et al, 2008 ; Ito et al, 2009 , 2011 ; Yan et al, 2017 ), and this conclusion has also been confirmed in human glaucoma patients (Gupta et al, 2006 , 2009 ; Dai et al, 2011 ; Hernowo et al, 2011 ; Shimazawa et al, 2012 ; Chen et al, 2013b ; Lee et al, 2014 ; Wang et al, 2015 , 2016 ; Zhang et al, 2016 ; Ersoz et al, 2017 ; Song et al, 2018 ; Xu et al, 2018 ; Li et al, 2019a ; Kosior-Jarecka et al, 2020 ). Weber et al used a laser-induced chronic glaucoma monkey model to explore changes in size, density, and number of LGN neurons during glaucoma.…”
Section: Transneuronal Degeneration In Glaucoma Brainmentioning
confidence: 68%